Analysis Fraudulent Financial Statement With Element Statement on Auditing Standards (SAS) No. 99 - Cahyono, Yadi; Nurmala, Putri (Universitas Pamulang, 2022)
The purpose of this research is to analyze the factors of fraudulent financial statement with element contained in the Statement on Auditing Standards (SAS) NO. 99. The dependent variable in this research is fraudulent financial statement. The independent variable of this research uses the elements contained in SAS NO. 99, namely pressure which is proxied with the financial target variable, opportunity which is proxied with the managerial ownership variable, rationalization which is proxied change external auditor. The population of this research were banking companies listed on the BEI in 2017-2020 as many as 45 companies. The sample selection method used in this research used purposive sample obtained as many as 24 companies that met the criteria. The regression model used was panel data regression analysis. Based on the results of the data analysis that has been carried out shows that the financial target has a significant negative effect on fraudulent financial statement. While managerial ownership and change external auditor not has effect on fraudulent financial statement.